The Effectiveness of the Prohibition of Money Politics on the Community as Recipients in the 2024 Legislative General Election in Bone Bolango Regency - Kaluku, Fahri; Darmawati, Darmawati; B, Sumiyati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The practice of money politics is still a serious problem in the implementation of General Elections in Indonesia, including in the 2024 Legislative General Election in Bone Bolango Regency. Money politics involves not only election participants as givers, but also the public as recipients, which is legally prohibited and can be sanctioned. This study aims to analyze the effectiveness of the regulation of the prohibition of money politics on the public as recipients in the 2024 Legislative General Election in Bone Bolango Regency. The research method used is empirical legal research with a qualitative approach. The data was obtained through interviews with election organizers, supervisory officials, and the voting community, and supported by secondary data in the form of laws and regulations and election supervision documents. The results of the study show that normatively the regulation of the prohibition of money politics has been clearly regulated in the Election Law, but in its implementation it has not been effective. This is due to low legal awareness of the public, economic factors, a permissive political culture towards money politics, and weak enforcement of sanctions against recipients. This study concludes that the effectiveness of the regulation of prohibition on money politics on the recipient community still needs to be improved through strengthening political education, participatory supervision, and consistent law enforcement to realize elections with integrity